2021
DOI: 10.1108/ics-12-2020-0205
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between e-government development, nation’s cyber-security commitment, business usage and economic prosperity: a cross-country analysis

Abstract: Purpose This study aims to propose a model to examine the relationships between e-government development, cybersecurity commitment, business usage and economic prosperity of the country. Design/methodology/approach Structural equation modeling was used to analyze the country-level variables to explain the second-order impact of e-government development through the mediating role of cybersecurity commitment. Findings Findings suggest that e-government development demonstrated a stronger association with cyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 71 publications
4
12
0
Order By: Relevance
“…Kwon et al (2013) demonstrated that senior management can impact employee attitudes and behaviors towards the organization's security approaches and techniques. Several studies (Kharlamov & Pogrebna, 2019; Krishna & Sebastian, 2021; McFadzean et al, 2006) have stated that the commitment of senior management is essential to enhancing the level of cybersecurity effectiveness in organizations. Hu et al (2012) argue that the commitment of senior management to cybersecurity positively motivates employees to engage in cybersecurity procedures and gain the skills required to increase the organization's security level.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Kwon et al (2013) demonstrated that senior management can impact employee attitudes and behaviors towards the organization's security approaches and techniques. Several studies (Kharlamov & Pogrebna, 2019; Krishna & Sebastian, 2021; McFadzean et al, 2006) have stated that the commitment of senior management is essential to enhancing the level of cybersecurity effectiveness in organizations. Hu et al (2012) argue that the commitment of senior management to cybersecurity positively motivates employees to engage in cybersecurity procedures and gain the skills required to increase the organization's security level.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…Previous studies (Al‐ma'aitah, 2017; Al‐Omoush et al, 2021; Zhu & Kraemer, 2005) have demonstrated that coercive pressure is a significant driver of the organizations' adoption of novel technologies such as Cloud ERPs, SCRM, and e‐business platforms. A study by Krishna and Sebastian (2021) indicated that organizations benefit from adhering to specific benchmark standards, such as ISO/IEC 27000, as this ensures that their online services are trustworthy and improves customer satisfaction. In the cybersecurity context, legal guidelines and restrictions set by governments are often important originators of coercive pressures on organizations.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations